PENINGKATAN KEBERANIAN SISWA BERKOMUNIKASI LANGSUNG DENGAN TAMU MELALUI ROLEPLAY PADA PEMBELAJARAN RESTAURANT SERVICE SMKN 1 SEWON - Suwantini Suwantini (Jurnal Ilmiah Guru Caraka Olah Pikir Edukatif, 2017)
This reportaims to foster self-confidence, independent, honest, and responsible, build interest in the subjects of restaurant service, in still character building andculture to optimize the learning process of restaurant service, provide students with knowledge and skills in areas of food and beverage services at the restaurant which are the task of the restaurants officers. They are expected to have competence in their field.This report was organized based on the method of classroom action researchwhich was conducted in the second semester of learning class XII student restaurant service catering in SMK 1 Sewon at academic year 2014/2015. The data collection techniques which are used in this study are questionnaires, and documentation study. Technical analysis of the data using the identification, data classification, description, and validation. The results show that: 1) the implementation of role play method in restaurant service process learning can make students to be more courageous to communicate directly with the guests. it can be seen in the attitudes and behavior of the student during the learning process. Students appear to be more confident incommunicating, independent, disciplined in doing the task and more responsible to them selves andthe group. 2) The courage to communicate directly with guests has increased after the implementation of role play learning method. It can be shown from the result, 7% of the student had no difficulty in communicating with guests on the first cycle, and it has incerased to 23% in on the second cycle. And there are significant increase on the third and fourth cycle, 52% and 72% respectively. 3) With having confidence, the student will be skilled in communicating directly with guests. It will successfully deliver the studentinto the world ofbusiness / industry and can also createt heir own jobs according to the field